2008
DOI: 10.2353/jmoldx.2008.070137
|View full text |Cite
|
Sign up to set email alerts
|

Amplification-Based DNA Analysis in the Diagnosis of Prosthetic Joint Infection

Abstract: Microbiological cultures are moderately sensitive for diagnosing prosthetic joint infection (PJI). This study was conducted to determine whether amplificationbased DNA methods applied on intraoperative samples could enhance PJI diagnosis compared with culture alone in routine surgical practice. Revision arthroplasty was performed for suspected PJI (n ‫؍‬ 41) and osteoarthrosis control (n ‫؍‬ 28) patients , and a diagnosis of PJI was confirmed in 34 patients. Amplification by polymerase chain reaction was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 23 publications
1
56
1
1
Order By: Relevance
“…16S rRNA gene real-time PCR results were in line with the conventional culture results in about 96 % of the studied patient cases. These findings seem to be consistent with previously published data on NAAT techniques, indicating a relatively wide range of sensitivity and specificity [8][9][10][11][12]. NAATs may reasonably expand the diagnostic panel and contribute to a higher recovery rate especially after antimicrobial use.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…16S rRNA gene real-time PCR results were in line with the conventional culture results in about 96 % of the studied patient cases. These findings seem to be consistent with previously published data on NAAT techniques, indicating a relatively wide range of sensitivity and specificity [8][9][10][11][12]. NAATs may reasonably expand the diagnostic panel and contribute to a higher recovery rate especially after antimicrobial use.…”
Section: Discussionsupporting
confidence: 91%
“…Only few studies have assessed the diagnostic utility of nucleic acid amplification test (NAAT) techniques in this context. The reported findings for different PJI-associated materials indicate a wide range of sensitivity (50-92 %) and specificity (65-94 %) [8][9][10][11][12][13]. Results from a recent study comparing 16S rRNA gene PCR and consecutive sequencing of sonication fluid with culture of synovial aspirates, tissue samples and sonication fluids reports that 16S rRNA gene PCR improved sensitivity [14].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular biology provided a diagnostic tool that showed its effectiveness, especially when antibiotics were administered before surgery or when fastidious bacteria were involved, particularly for the diagnosis of endocarditis (4). For BJI diagnosis, broad-range 16S rRNA gene PCR has shown higher, lower, or equivalent sensitivity compared with conventional culture methods, but sometimes to the detriment of specificity (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…In a review of 34 patients with confirmed prosthetic joint infection Vandercam et al found that PCR was positive in 31 of 34 patients (91.2%), compared to positive microbiological culture in 22 of 34 patients (64.7%). Of import, eight of the nine patients with positive PCR but negative culture results had received antibiotic therapy in the prior ten days (Vandercam, et al 2008). Despite these promising results, the weakness of 16s ribosomal RNA PCR techniques is the low specificity and high false positive rate.…”
Section: Molecular Techniquesmentioning
confidence: 99%